Corporate taxation and total factor productivity: Evidence on a non-linear relationship - Hang T. T. Nguyen (Arbeitskreis Quantitative Steuerlehre (arqus), 2024)
This paper presents an empirical analysis of the relationship between the corporate income tax (CIT) and the growth of total factor productivity (TFP) within European firms. Using data from the AMADEUS database over the 2005-2013 period, I measure the TFP of each firm using Wooldridge's (2009) methodology, alongside four alternative approaches introduced by Olley and Pakes (1996), Levinsohn and Petrin (2003), Ackerberg et al. (2015), and ordinary least squares (OLS) regression. The baseline investigation follows the TFP catch-up framework of Griffith et al. (2009). While my analysis corroborates prior findings indicating a negative relationship between CIT rates and the speed with which firms converge to the productivity frontier (productivity catch-up, Gemmell et al., 2018), it also uncovers a positive association between CIT rates and the average growth of productivity. Thus, the evidence reveals a non-linear relationship between corporate taxation and firms' productivity growth. Heterogeneity tests show that corporate income taxation is more relevant for the productivity growth of small-scale enterprises and domestic entities. These findings are robust to a variety of alternative specifications and tests.
Keywords: 330